2015
DOI: 10.1007/s11104-015-2523-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of continuous drought stress on soil respiration in a tropical rainforest in southwest China

Abstract: Background and aims Drought is predicted to have a profound impact on soil respiration. This study aimed to assess the effects of long-term precipitation decrease on soil respiration in a tropical rainforest. Methods A precipitation reduction experiment was conducted in a tropical forest in southwest China at the beginning of 2011. Soil respiration and environmental parameters were measured monthly for three years. Results The continuous precipitation reduction treatment did not affect the seasonal patterns of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 55 publications
4
42
1
Order By: Relevance
“…Soil respiration is one of the major pathways of C exchange between the biosphere and the atmosphere (Inglima et al., ), and largely determines terrestrial C sequestration (Chen, Post, Norby, & Classen, ; Zhou et al., ). Soil respiration in response to changing precipitation can substantially affect soil C pool (Ford, McGee, Scandellari, Hobbie, & Mitchell, ; Zhang et al., ). Our findings of suppressed soil respiration under both advanced and delay precipitation peaks during the growing season, in combination with their additive effects, indicate that less soil C will be released from arid and semiarid ecosystems to the atmosphere under changing precipitation regimes in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Soil respiration is one of the major pathways of C exchange between the biosphere and the atmosphere (Inglima et al., ), and largely determines terrestrial C sequestration (Chen, Post, Norby, & Classen, ; Zhou et al., ). Soil respiration in response to changing precipitation can substantially affect soil C pool (Ford, McGee, Scandellari, Hobbie, & Mitchell, ; Zhang et al., ). Our findings of suppressed soil respiration under both advanced and delay precipitation peaks during the growing season, in combination with their additive effects, indicate that less soil C will be released from arid and semiarid ecosystems to the atmosphere under changing precipitation regimes in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, WW did not change monthly measured soil moisture, but significantly increased soil respiration (Figure 2d,f). Several precipitation manipulation experiments also suggested that soil respiration was not affected by increased soil moisture (e.g., Davidson et al, 2008;Deng et al, 2012;Zhang et al, 2015). The decoupling between soil respiration and soil moisture change could be attributed to limitation of other environmental variables to soil respiration (Vasconcelos et al, 2004;Zhang et al, 2015), the adaption of soil microbes and plants to altered soil moisture (Bouskill et al, 2013;Kozlowski & Pallardy, 2002;Kruse, Turnbull, & Adams, 2012), and so on.…”
Section: Effects On Soil Respirationmentioning
confidence: 99%
“…Thus, soil respiration does not always respond positively to precipitation change. In some studies, drought has been found to increase soil respiration by alleviating the oxygen deficit (Liu, Liu, et al, ; Zhang et al, ). In contrast, increased precipitation has been found to decrease soil respiration in a mesic ecosystem (Suseela & Dukes, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a 3 year soil moisture exclusion that reduced rainfall by 50% in five 100 m 2 plots in a tropical forest in Southwestern China showed soil moisture declined by 4‐5.5% during the wet season, and 1‐5% during the dry season, with no effect on soil temperature. In this study, soil respiration increased by 30% during the rainy season over 3 years, with no effect during the dry season [ Zhang et al ., ], again suggesting that C stocks in wetter soils are more vulnerable to drying. In a 100% precipitation exclusion experiment in 0.5 m 2 plots in Costa Rican forests and in lab incubations using a range of soil moistures, soil respiration increased following intense short‐term reductions in precipitation [ Waring and Hawkes , ].…”
Section: Review Of Global Change Effects On Tropical Ecosystemsmentioning
confidence: 99%